(untitled) (Global Journal of Medical Research, 2020)
Coronary artery disease (CAD) is one of the leading causes of morbimortality worldwide. In patients with diabetes mellitus type 2 (DM2), CAD is more likely to be a complex disease and often requires cardiac surgery. Furthermore, perioperative blood glucose levels control is associated with the followingoutcomes: surgery success, mortality, and infection postoperative. This is a retrospective study, we have collected data form, 43 patients, between 2015 and 2017, with diabetes type 2 and who had passed through a Coronary Artery Bypass Grafting. Those with infection postoperative had a glycohemoglobin 7, 9 (SD ±1,4), and those without infection had an HbA1c 7, 25 (SD ±0,94) and a p-value from 0,039. Adding this was identified that the average of creatinine clearance in patients with the infectious disease was 59 (SD ±21, 3) and 67 (SD ±26) in those without infection, calculated a p-value from 0,039. High levels of Hb1Ac are a predictor of infection disease postoperative.